2010
DOI: 10.1177/1473325010382325
|View full text |Cite
|
Sign up to set email alerts
|

To Offer Hope You Must Have Hope

Abstract: As women on parole and probation transition from correctional facilities to the community, they face many threats to reintegration. Reintegration counsellors offer support to individuals on parole and probation who are re-entering the community. Working closely with a marginalized population places counsellors at risk for burnout and hopelessness. Research indicates that hope can serve as a sustaining and motivating factor when facing difficult working contexts. Further, a large body of research consistently c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Hope for change in more direct social work practice should also be evident. Hope is positively related to coping with stress for social workers and coping with both day-to-day, and sometimes extraordinary client situations are likely to require a healthy level of hope (Schwartz, Tiamiyu, and Dwyer 2007;Flesaker and Larsen 2010). As we have noted, as well as strengths, clients may present personal, family and resource problems that can be daunting for many social workers.…”
Section: Further Implications Of Hope Theory and Research For Social mentioning
confidence: 87%
See 3 more Smart Citations
“…Hope for change in more direct social work practice should also be evident. Hope is positively related to coping with stress for social workers and coping with both day-to-day, and sometimes extraordinary client situations are likely to require a healthy level of hope (Schwartz, Tiamiyu, and Dwyer 2007;Flesaker and Larsen 2010). As we have noted, as well as strengths, clients may present personal, family and resource problems that can be daunting for many social workers.…”
Section: Further Implications Of Hope Theory and Research For Social mentioning
confidence: 87%
“…can benefit from helping (Coppock et al 2010), whilst several small-scale qualitative research studies show that professional care giving relationships are a key source of client hope (Eliott and Olver 2002;Flesaker and Larsen 2010). Several other research studies suggested that hope theory has served as a framework for developing successful help with individuals, couples, families and groups (Lopez et al 2000;Cheavens et al 2006Worthington et al 2007).…”
Section: Definitions Of Hope -Hope As Emotion And/or Cognitionmentioning
confidence: 94%
See 2 more Smart Citations
“…Indeed, hope and hopelessness are increasingly seen as fundamental for social work and care professionals (Collins, 2015; Flesaker & Larsen, 2012; Krumer‐Nevo, 2020). Coordinators in the study described how maintaining their own hope in the future enabled them to offer hope to the families.…”
Section: Discussionmentioning
confidence: 99%